2021
DOI: 10.5603/ep.a2021.0071
|View full text |Cite
|
Sign up to set email alerts
|

The impact of levothyroxine on thyroid autoimmunity and hypothalamic–pituitary–thyroid axis activity in men with autoimmune hypothyroidism and early-onset androgenetic alopecia

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Endokrynologia Polska" are listed in PubMed. The final version may contain major or minor changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…These were all case-control studies. The results showed that men with early-onset AGA may experience less benefit from rosuvastatin [ 64 ], metformin [ 65 , 66 ], lisinopril [ 67 ], levothyroxine [ 68 ], Vitamin D [ 69 ], or bromocriptine [ 70 ] when treating dyslipidemia, prediabetes, hypertension, autoimmune hypothyroidism, autoimmune thyroiditis, or prolactin excess, respectively, compared to the contemporaries without alopecia. However, one exception was noted, as the impact of metformin on gonadotroph secretory function appeared to be stronger in men with early-onset AGA compared to those with normal hair growth [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…These were all case-control studies. The results showed that men with early-onset AGA may experience less benefit from rosuvastatin [ 64 ], metformin [ 65 , 66 ], lisinopril [ 67 ], levothyroxine [ 68 ], Vitamin D [ 69 ], or bromocriptine [ 70 ] when treating dyslipidemia, prediabetes, hypertension, autoimmune hypothyroidism, autoimmune thyroiditis, or prolactin excess, respectively, compared to the contemporaries without alopecia. However, one exception was noted, as the impact of metformin on gonadotroph secretory function appeared to be stronger in men with early-onset AGA compared to those with normal hair growth [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some theories propose a connection between MPA and metabolic syndrome, insulin resistance, and/or hypogonadism, but this link is not universally accepted [ 66 , 67 ]. Early-onset androgenetic alopecia has been associated with low testosterone and dehydroepiandrosterone levels, and testosterone replacement in hypogonadism may contribute to a decrease in antithyroid antibodies in these patients [ 67 , 68 ]. A small study conducted in 2021 on autoimmune hypothyroidism patients, suggested that male patients without baldness may have a better response to TH replacement therapy compared to those with MPA [ 68 ].…”
Section: Reviewmentioning
confidence: 99%
“…Early-onset androgenetic alopecia has been associated with low testosterone and dehydroepiandrosterone levels, and testosterone replacement in hypogonadism may contribute to a decrease in antithyroid antibodies in these patients [ 67 , 68 ]. A small study conducted in 2021 on autoimmune hypothyroidism patients, suggested that male patients without baldness may have a better response to TH replacement therapy compared to those with MPA [ 68 ]. However, more evidence is needed to support this finding.…”
Section: Reviewmentioning
confidence: 99%